2015
DOI: 10.1136/jnnp-2014-308284
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric diagnoses underlying the phenocopy syndrome of behavioural variant frontotemporal dementia

Abstract: This is the first study thoroughly exploring psychiatric causes of the bvFTD phenocopy syndrome, revealing that in most cases multiple factors played a contributory role. Our study gives arguments for neurological and psychiatric collaboration when diagnosing bvFTD. Prompt diagnosis of treatable psychiatric conditions is to be gained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 22 publications
3
53
0
8
Order By: Relevance
“…Systematic screening for C9orf72 in all patients would be interesting for future analyses of the cohort. Furthermore, the so-called phenocopy syndrome, possibly without a neurodegenerative origin, can mimic real bvFTD [45,46,47]. …”
Section: Discussionmentioning
confidence: 99%
“…Systematic screening for C9orf72 in all patients would be interesting for future analyses of the cohort. Furthermore, the so-called phenocopy syndrome, possibly without a neurodegenerative origin, can mimic real bvFTD [45,46,47]. …”
Section: Discussionmentioning
confidence: 99%
“…There are reports of C9orf72 expansion carriers with slowly progressing disease that satisfy criteria for the phenocopy syndrome,3 although presumably these cases would show TDP-43 and di-peptide repeat protein deposition at autopsy. A recent study examined the personality and psychiatric background of phenocopy cases and found that many have a complex medical history including personality and psychiatric illnesses, although C9orf72 testing was not performed in this cohort 4. Another theory exists that these cases represent decompensated autism, and while there are many similarities between the conditions, this remains to be proven.…”
Section: Discussionmentioning
confidence: 94%
“…16 Patients with bvFTD phenocopy syndrome who fail to progress have increased rates of mood disorders, substance abuse, obsessive-compulsive personality traits, Asperger syndrome traits, or recent intense life events that likely contribute to the observed behaviors. 17 Comment. There is commonly a long delay between the onset of symptoms and time of presentation, given the subtle nature of the personality and behavior changes that are the hallmark of early FTD.…”
Section: Diagnostic Challenges In Behavioral Variant Of Frontotemporamentioning
confidence: 99%